The self-management instrument for breast cancer patients undergoing adjuvant therapy: Development and psychometric testing using the COSMIN methodology - Lingying Jia; Jiajia Qiu; Ping Li; Lijuan Yang; Lei Xu; Xiaoju Zhang; Yan Hu (Elsevier, 2023)
Objective: This study aims to develop and test the self-management instrument for breast cancer patients undergoing adjuvant therapy (SMAT-B). Methods: After a qualitative interview with 29 patients and two rounds of Delphi expert consultation with 15 experts, 49 items were initially generated. Before item reduction, another structured interview was conducted for content validity. Item analysis and exploratory factor analysis (n ​= ​377) were used for item reduction. After that, internal consistency, split-half reliability, test-retest reliability (n ​= ​30), measurement error, construct validity, and structural validity (n ​= ​342) were preliminarily evaluated using the COnsesus-based Standards for the selection of health Measurements INstruments guidelines. Results: The final version of SMAT-B includes 7 dimensions and 31 items after item reduction. The testing results suggested that SMAT-B had good internal consistency (Total Cronbach's α ​= ​0.952), good split-half reliability (Spearman-Brown coefficient ​= ​0.904), good stability (Total intraclass correlation coefficient = ​0.797), acceptable measurement error (SEM ​= ​5.28), and acceptable construct validity (Standardized root mean square residual ​= ​0.055). The hypotheses of construct validity were all verified to a certain extent (r ​> ​0.20, P ​< ​0.01). Conclusions: The 31-item SMAT-B, developed in interviews with patients and consultation with experts, demonstrated good psychometric properties and can be recommended for researchers and clinicians for further validity testing and evaluation of the self-management ability of breast cancer patients. Trial registration: ChiCTR2100052868.